Prevalence of alveolar bone deffect pattern in periodontitis patients with diabetes mellitus using bitewing radiography - Lidya I. Nainggolan; Lavaneya Gunasagaran (DiscoverSys Inc., 2018)
Objective: The purpose of this study is to know the prevalence of horizontal pattern bone deffect compare to vertical pattern that found in periodontal disease.Material and Methods: In this study, sample selected by purposive sampling according to inclusion criteria, samples with periodontitis that diagnosed clinically approved by periodontist, and the sample also have diabetic diseases that having measure their sugar level blood test 3 months before the study, and then measure it again before taking the radiograph.Results: The horizontal pattern that found in periodontitis in patient that sustain diabetes mellitus in this study might occur due to bone damage that developed in long period and without treatment.Conclusion: This study shows the prevalence of bone damage pattern was the pattern of horizontal obtained 76.3%, vertical pattern is found at 23.7%. The horizontal pattern that found mostly in periodontitis in patient that sustain diabetes mellitus in this study might occur due to bone damage that developed in long period and without treatment.